Identifikasi Pembealajaran Ipa Dan Penggunaan E-Modul Di Smp Negeri 2 Kabun, Rokan Hulu - Luthfi Qolbiah; Siti Robiah; Nurkhairo Hidayati (Jurnal Ilmu Pendidikan Biologi dan IPA, 2026)
This study aims to describe the condition of science learning and the need for e-module development at SMP Negeri 2 Kabun. A descriptive mixed-methods approach was employed. Data were collected through interviews with two science teachers and questionnaires administered to 30 students from grades VII, VIII, and IX. The results indicate that students’ understanding and learning experiences in science are categorized as high (73.2%). However, the use of learning media remains low (36%), students’ need for science e-modules is very low (27%), and learning style support is also very low (20.4%). These findings highlight the need to develop interactive science e-modules to enhance students’ motivation, conceptual understanding, and independent learning.